The Legal Vacuum on Access to Higher Education for Refugees in Indonesia: Islamic Claim for Aceh Responsibility - Aiyub Kadir, M. Yakub; Rivaldi, Aditya; Farsia, Lena; Bantasyam, Saifuddin (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
This article investigates the prospect of granting refugee students the opportunity to enroll in higher education in Indonesia, particularly Aceh. Due to the vacuum of law on the rights for higher education for refugees. This article explores the possibility of religious claim on the rights for higher education for refugees. This study aims to prove that amidst the vacuum of law on the higher education rights for the refugee, Indonesia is still legally, socially, and religiously responsible in providing higher education access for refugees. Using doctrinal and quantitative legal research. This research demonstrated that Indonesia should be able to provide higher education for refugees by minimally but significantly changing the meaning of several of its higher education regulations. The responsibility bear by Indonesia is stipulated clearly in its constitutional preamble, as well as article 28(C)1 of Indonesia constitution. This report also confirmed that Aceh, with its past and present position, meets the requirement of an “Islamic Land,” and hence has a fundamental religious commitment to give refugees with the same rights as its inhabitants. This report also suggests technical collaboration or assimilation with the Global Education Convention system, as well as combining the Paket C and the UNESCO Qualifications Passport for Refugee systems to address any refugee's paperwork and qualification issues. This study contributes to the advocacy and support for significant humanitarian aid that Indonesia, particularly Aceh, may provide to refugees in order to help them prepare for a better future.